Perampasan Tanah dan Kerusakan Lingkungan Hidup atas Nama Hilirisasi; Problematika dan Urgensi Penegakkan Hukum - Putri Nasution, Zakiyah Dwi; Priyono, Ery Agus (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the practices of land grabbing and environmental degradation occurring in downstream processing projects of natural resources in Indonesia, as well as the urgency of legal enforcement to address these issues. The methodology employed is normative legal research with a qualitative approach, based on literature review of legislation, court decisions, and relevant academic sources. The findings indicate that downstream processing is often used as a justification for forced land acquisition and ecological destruction, violating Articles 28H and 33 of the 1945 Constitution, as well as Law No. 5 of 1960 and Law No. 32 of 2009. The study concludes that weak law enforcement is a key factor contributing to structural injustice, thus highlighting the need for regulatory reform, stronger oversight, and a legal system that is fair, transparent, and participatory.